2018
DOI: 10.2174/1381612824666180727115222
|View full text |Cite
|
Sign up to set email alerts
|

Current Rapid-Onset Antidepressants and Related Animal Models

Abstract: Depression is a common mental disease, and it is one of the most crippling diseases in the world. Although current pharmacotherapies contribute to the treatment of depression, the high incidence of a partial responses or no responses, and delayed onset of the antidepressants, make many patients to experience unsatisfactory results from treatment. In view of the high suicide rate during the period of drug onset, it is critical to find antidepressant drugs with rapid onset for the treatment of depression. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In our results, depression behavioral detection was performed with three detection models (OFT, FST and TST), which are in line with the internationally recognized animal detection model of affective disorder. 34 Studies have shown that quercetin, a major component of TFA, has antidepressant effects by improving oxidative stress, and hyperoside has antidepressant effects by regulating HPA axis activity and antioxidant activity. 35 , 36 Consistently, our research showed that TFA treatment rescued depressive-like behaviors in CS mice.…”
Section: Discussionmentioning
confidence: 99%
“…In our results, depression behavioral detection was performed with three detection models (OFT, FST and TST), which are in line with the internationally recognized animal detection model of affective disorder. 34 Studies have shown that quercetin, a major component of TFA, has antidepressant effects by improving oxidative stress, and hyperoside has antidepressant effects by regulating HPA axis activity and antioxidant activity. 35 , 36 Consistently, our research showed that TFA treatment rescued depressive-like behaviors in CS mice.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many researchers have been actively focusing on the neurobiological processes involved in addiction, tolerance, dependence, and withdrawal of opioids [ 4 , [6] , [7] , [8] ]. In addition, several addictions and addictive treatments of opioid-related disorders have also recently surfaced through the diverse pharmacological, psychological, social intervention approaches such as methadone maintenance therapy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above results in vitro, we further explored the related phenomena and mechanisms by establishing a mouse model of depression. CUMS, which induces long-lasting depressive-like behavior for up to several months, is a well-established model of depression in rodents and can be reversed by chronic treatments with traditional antidepressant agents 43 45 . Compared to those of males, females have higher incidence rates of major depressive disorder 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%